Neurosyphilis - Two clinical cases - Ribeiro, Ana (2000)
ln the early 2(Jh century, syphilis was a leading cause of neurologic and cardiovascular disease. After the introduction of penicillin the number of cases with Central Nervous System (CNS) envolvement, neurosyfphlis, declined radically. However, in the last decades, with the emergence of the human immunodeficiency vírus (HIV) infection, we have seen a significant increasing number of new cases. Through the description of two cases of neurosyphilis, representative of the paradigm of the actual situation, (namely the presence or absence of concomitant HIV infection) the authours try to show the differences between these two groups of patients, namely: the natural history of syphilis/ frequency of symptomatic neurosyphilis/atypical forms of disease/diagnosis difficulty/failure of conventional penincillin therapy. The authours persist in the diagnostic difficulty of the CNS involvement and the need to develop newer tests with high sensibility and specificity to neurosyphilis such as Polymerase Chain Reaction (PCR) or monoclonal antibodies directed against T. Pallidum antigens.